Faktor Orang Tua dalam Perilaku Merokok Remaja: Studi Perbandingan di Daerah Rural dan Urban - Yenti, Melisa; Haq, Arinil; Putri, Anggela Pradiva; Putri, Hanifa Eka; Sari, Dela Desmita; Erika, Shabrina (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2025)
Background. Adolescent smoking can lead to various health problems. The percentage of adolescents smoking in rural areas (4.34%) is higher than in urban areas (3.14%). Aim. The study aimed to determine the difference in the role of parental factors on adolescent smoking behavior in rural and urban areas. Method. The study used a cross-sectional comparative design. Conducted in June-July 2024 at one rural high school and one urban high school. The sample amounted to 57 respondents in each school with simple random sampling technique. Data analysis used Mann-Whitney test to test the difference between the two regions. Result. It was found that adolescent smoking behavior was more in rural areas (63.2%) than urban areas (33.3%). Factors associated with both regions include maternal education (p=0.001 and p=0.001), parental income (p=0.003 and p=0.016), and parental influence (p=0.028 and p=0.025). Only paternal education (p=0.026) and maternal occupation (p=0.003) were associated in urban areas. There were different factors between the two regions including mother's education (Sig=0.033) and parents' income (Sig=0.009). Differences in factors between urban and rural areas were found in maternal education, parental income and attitudes towards smoking policies. Parents need to be more active in monitoring children's behavior, providing education about the dangers of smoking, and being a positive example by creating a smoke-free home environment.